Synthese von 1,4-Diazepino[1,2-a]-indolen - Hans Peter Härter; Othmar Schindler (CHIMIA)
Condensation of 1-(3-aminopropyl)-3-methyl-indole (1) with acetaldehyde or benzaldehyde by the Mannich reaction gave 1,4-diazepino[1,2-a]-indoles 2 and 3 respectively. The 1,4-diazepino[1,2-a]indole 9 was obtained by analogous acidcatalyzed cyclo-condensation of 1 with dimethyl-2-dimethoxyethylmalonate (8), and 6,17, and 19 were obtained by intramolecular condensation of 5, 15, and 16 respectively. All these lactames could be readily reduced to the corresponding bases 7, 12, 18 and 20. Bischler-Napieralsky cyclization of 23 gave the diazepinoindole-butanoic acid derivative 25 as main product, together with the fully cyclized 24. Compound 25, after reduction, gave directly the diazepinoindole 26, which was also obtained by reduction of compound 24.